Optimizing esthetic zone periodontal regeneration in a 1-2‐wall infrabony defect using recombinant human platelet‐derived growth factor BB and β‐tricalcium phosphate: A case report - Kantapon Rattanaprukskul; Rodrigo Neiva; Jonathan Korostoff (Wiley, 2024)
Abstract Objective Periodontitis is an inflammatory condition induced by subgingival bacterial dysbiosis, resulting in inflammatory‐mediated destruction of tooth‐supporting structures, potentially leading to the formation of infrabony defects. This case report describes the treatment of a patient who presented with a combination 1-2‐wall defect on tooth 21. To maintain the residual periodontal attachment and minimize esthetic consequences, a regenerative approach was performed using recombinant human platelet‐derived growth factor‐BB (rh‐PDGF‐BB) and β‐tricalcium phosphate (β‐TCP). Materials and Methods At the time of postscaling/root planing reevaluation, a 34‐year‐old Asian male initially diagnosed with molar/incisor pattern stage III grade C periodontitis exhibited a 6‐mm residual probing depth on the mesiopalatal aspect of tooth 21. Periodontal regenerative surgery was performed using rh‐PDGF‐BB with β‐TCP, without the use of a membrane. Results At the 1‐year follow‐up, a significant reduction in probing depth and radiographic evidence of bone fill were observed. Additionally, re‐entry surgery for implant placement at site tooth 23 confirmed bone fill in the defect on tooth 21. Conclusion These results demonstrate the efficacy of rh‐PDGF‐BB with β‐TCP in enhancing periodontal regeneration and support its use as a treatment option when treating poorly contained infrabony defects in the esthetic zone.